THE ROLE OF TRANSFORMATION ON HINDU TEACHERS IN CHARACTER-BASED HINDU LEARNING DURING THE COVID-19 PANDEMIC THROUGH CATUR PARAMITA TEACHINGS (CASE STUDY IN SD NEGERI 5 BATUBULAN) - Ni Wayan Ariantini; Ni Komang Sutriyanti; Ida Ayu Adi Armini (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2022)
This paper aimed to describe and explore the role of Hindu teachers in character education and transforming Hindu education through the teachings of Catur Paramita in Elementary Schools in shaping the character of students, in order to obtain the next generation of the nation with morals and noble character. The results showed that first, the role transformation of Hindu religion teachers in character-based Hindu learning in the post-Covid-19 pandemic through the teachings of Catur Paramita (Study of Case: SD Negeri 5 Batubulan) namely: the role transformation of Hindu religion teacher through the teachings of Maitri, Karuna, Mudita and Upeksa, the transformation of Hindu religion teacher as a model, and the role transformation of the Hindu religion teacher as an evaluator. Second, the obstacles faced by Hindu teachers come from: internal constraints, namely innate factors, emotional factors, and interest factors as well as external constraints, namely the family environment, school environment, society environment, and mass media. Third, the efforts the efforts that can be done are: providing an understanding in teachings about Catur Paramita, Optimizing the teaching activities of Catur Paramita and astablishing a good communication with parents and students.